2001
DOI: 10.1021/np000468f
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenated Sesquiterpenoids from a Nonpoisonous Sardinian Chemotype of Giant Fennel (Ferula communis)

Abstract: The roots of the nonpoisonous chemotype of giant fennel (Ferula communis) from Sardinia afforded a novel cadinanetriol (1), whose structure was established by spectroscopic data and confirmed by synthesis from the E,E-Delta (1(10),5) germacradiene allohedycariol. A number of known compounds were also identified. Despite the lack of morphological differences, a broad chemical diversity exists within giant fennel, underlying the contrasting data on its poisonous properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…The daucane esters 1a, b-4 and jaeskeanadiol (1c) were available from previous studies Appendino et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daucane esters 1a, b-4 and jaeskeanadiol (1c) were available from previous studies Appendino et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…The latter is limited to some niches in Southern Sardinia, while the former is more widespread, and encompasses two distinct chemotypes (Appendino, 1997;Sacchetti et al, 2003). Since daucane esters are typical constituents of one of these chemotypes (Appendino et al, 2000) and of F. arrigonii , a number of these compounds were available, and were screened for anticancer activity. We present evidence that certain daucanes exert antiproliferative effects, and that interaction with the type II estrogen-binding sites (EBS) underlies this activity.…”
Section: Introductionmentioning
confidence: 99%
“…The reported compounds are mainly coumarin derivatives and sesquiterpene alcohol esters, most of which are aromatic esters bearing the daucane skeleton [9][10][11].…”
mentioning
confidence: 99%
“…The oil from the aerial parts of F. flabelliloba contained δ-cadinene (13.2%), α-cadinol (12.0%) and cadina-4,1(10)-dien-8β-ol (10.9%), and α-pinene (10.0%), as the major components [11].…”
mentioning
confidence: 99%
“…The reported compounds were mainly coumarins and sesquiterpene esters; most of these exhibited the daucane skeleton. 1,[5][6][7][8][9][10][11] Conversely, only a few studies have reported the chemical composition of Ferula essential oils. They concerned the species F. flabelliloba, 12 F. stenocarpa, 13 F. galbaniflua 14 and F. gummosa 15 from Iran and F. elaeochytris from Turkey.…”
Section: Introductionmentioning
confidence: 99%